Upaya Peningkatan Hasil Belajar Bola Voli Menggunakan Pendekatan Bermain - Zaki Divo Marzuki; Lutfi Irawan Rahmat; Edi Irwanto; Riska Fita Lestari (MAN Insan Cendekia Jambi, 2025)
This research aims to improve volleyball educational outcomes through the application of engaging learning methodologies within the framework of Physical Education and Health Education.Basic techniques including the down serve, top serve, smash, block, down pass, and up pass were studied. An intervention designed to improve volleyball learning outcomes through an engaging methodology was conducted at Ma'arif Wongsorejo Junior High School during the 2024/2025 academic year.The results of this study demonstrated significant improvements in the educational outcomes of students at Ma'arif Wongsorejo Junior High School who participated in the cat-and-cat game methodology.A comprehensive analysis covering three aspects of educational outcomes—psychomotor, affective, and cognitive—initially revealed that among a group of 30 students, 18 students passed while 12 failed, representing a psychomotor achievement rate of 24%, affective at 20.6%, and cognitive at 22.8%. The average score at the beginning of the study was 60%, indicating that 40% of students failed. In cycle I, significant improvements in educational outcomes were recorded, with 24 students passing and 6 failing, resulting in an average score of 80%, with 20% of students failing. The psychomotor, affective, and cognitive achievement rates were 25.1%, 22%, and 25.5%, respectively.In Cycle II, students demonstrated further progress in educational outcomes, with 27 students passing and 3 failing, culminating in psychomotor, affective, and cognitive achievement levels of 27.4%, 25.5%, and 26.4%, respectively, and an average score of 90%, culminating in a 90% pass rate among students, thus concluding the action research without progressing to additional cycles.